Gendered pathways to resilience and food security: Insights from gender-transformative socio-technical innovation bundles in Nakuru County - Lutomia, Cosmas Kweyu; Ketema, Dessalegn; Morra, Linet; Nchanji, Eileen Bogweh (2025)
This infographic presents evidence from Nakuru County on the adoption of gender-transformative socio-technical innovation bundles (GTSTIBs) and their effects on productivity, resilience, empowerment, and food security. Findings highlight strong uptake of innovations, higher yields on demonstration farms, and notable resilience gains among adopters. Gendered patterns further reveal persistent gaps, with women often disadvantaged in food security despite high participation in trainings